Analysis of panel physician inquiries to U.S. TB Centers of Excellence, 2018–2022 - E. Leithead IV; S. Subramanian; K. Pimenta; N.D. Goswami; A. Patrawalla; A. Lardizabal; C. Haley; L. Chen; L. Armitige; B. Seaworth; B. Sylvester; R. Bhavaraju (IJTLD Open)
BACKGROUND: Applicants seeking entry into the United States are examined overseas for TB by panel physicians and international immigration clinicians guided by Centers for Disease Control and Prevention (CDC) TB Technical Instructions. To support this effort, CDC-funded TB Centers of Excellence (COEs) provide web-based expert consultation, with documentation stored in a medical consultation database (MCD). MCD analysis can reveal inquiry trends among panel physicians worldwide. METHODS: TB-related queries in the COE MCD from January 1, 2018, to December 31, 2022, were analyzed using a descriptive coding scheme developed through inductive analysis, allowing multiple themes per entry. RESULTS: A total of 215 queries from 126 patients in 28 countries were analyzed. Major themes included evaluating diagnostic criteria, tailoring treatment, and managing comorbidities or adverse reactions. Diagnostic questions (n = 104, 48.4%) included mycobacterial culture, smear, and radiology interpretation. Treatment tailoring inquiries involved optimizing the initial regimen (n = 89, 41.4%) or modifying existing regimens (n = 26, 12.1%). Additionally, 50 consultations (23.2%) mentioned comorbidities, while 47 (21.9%) described adverse reactions. CONCLUSION: The MCD analysis identified topics where TB expertise was provided in overseas medical evaluation. These topics highlight opportunities for targeted panel physician education to improve the health of individual applicants and advance U.S. TB elimination efforts.